2001
DOI: 10.1093/gerona/56.9.b375
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in the Autophagic Proteolysis of Rat Isolated Liver Cells: Effects of Antiaging Dietary Restrictions

Abstract: Autophagy is a process that sequesters and degrades organelles and macromolecular constituents of cytoplasm for cellular restructuring and repair and as a source of nutrients for metabolic use in early starvation. The effects of two antiaging dietary regimens (initiated in rats at the age of 2 months), namely, 40% dietary restriction (DR) and every-other-day ad-libitum feeding, that exhibited different effects on metabolism and similar effects on longevity on the age-related changes in the regulation of autoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(72 citation statements)
references
References 34 publications
3
67
0
Order By: Relevance
“…Compromised autophagy with age was initially described in this organ (Bergamini & Kovacs, 1990; Donati et al., 2001) and working with liver allowed us to recover enough organelles for biochemical assays. We isolated APG (enriched in LC3‐II and p62; note that the low amounts of LAMP1 and cathepsin observed in this fraction could represent amphisomes [resulting from fusion of APG and late endosomes]) and AUT (also enriched in both markers but with higher abundance of lysosomal markers (LAMP1, CathB, and mucolipin; Figure 4a ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compromised autophagy with age was initially described in this organ (Bergamini & Kovacs, 1990; Donati et al., 2001) and working with liver allowed us to recover enough organelles for biochemical assays. We isolated APG (enriched in LC3‐II and p62; note that the low amounts of LAMP1 and cathepsin observed in this fraction could represent amphisomes [resulting from fusion of APG and late endosomes]) and AUT (also enriched in both markers but with higher abundance of lysosomal markers (LAMP1, CathB, and mucolipin; Figure 4a ).…”
Section: Resultsmentioning
confidence: 99%
“…Autophagic flux (combination of autophagosome biogenesis and their degradation by lysosomes) decreases in an age‐dependent manner in organs such as liver (Bergamini & Kovacs, 1990; Donati et al., 2001). Induction of autophagosome formation in response to liver‐specific stimuli such as glucagon decreases with age (Bergamini & Kovacs, 1990), but despite reduced biogenesis the overall number of autophagosomes is higher in old livers (Stupina, Terman, Kvitmitskaia‐Ryzhova, Mezhiborkaia & Zherebitskii, 1994) due to compromised maturation of autophagosomes into autolysosomes with age (Terman, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Although macroautophagy, a nonselective form of autophagy, also decreases with age (Terman, 1995;Donati et al, 2001), the fact that the lysosomal population analyzed has been shown to be very active for CMA and that only a subset of oxidized proteins was detected in lysosomes encouraged us to analyze the role of CMA in the removal of oxidized proteins.…”
Section: Oxidized Proteins In Lysosomesmentioning
confidence: 99%
“…Similar assays to the ones described above confirmed that the oxidized proteins were of extralysosomal origin and could be degraded by the lysosomal proteases (our unpublished data). The last panel of Figure 1B shows the specificity of the antibody used in these studies against the carbonyl groups, which in nonderivatized samples only weakly cross-reacted with a single protein (compare signal in derivatized (lane 7) and nonderivatized samples (lane 8).Although macroautophagy, a nonselective form of autophagy, also decreases with age (Terman, 1995;Donati et al, 2001), the fact that the lysosomal population analyzed has been shown to be very active for CMA and that only a subset of oxidized proteins was detected in lysosomes encouraged us to analyze the role of CMA in the removal of oxidized proteins. …”
mentioning
confidence: 97%
See 1 more Smart Citation